2011
DOI: 10.1242/jeb.053421
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenomic signatures of spatiotemporal memories in time-trained forager honey bees

Abstract: SUMMARYHoney bees can form distinct spatiotemporal memories that allow them to return repeatedly to different food sources at different times of day. Although it is becoming increasingly clear that different behavioral states are associated with different profiles of brain gene expression, it is not known whether this relationship extends to states that are as dynamic and specific as those associated with foraging-related spatiotemporal memories. We tested this hypothesis by training different groups of forage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 57 publications
5
47
0
Order By: Relevance
“…Perhaps differences in the expression of genes such as odour-binding protein 4 (obp4) reflect some of the differences in the sensory aspects of these two types of scouting. The gene obp4 showed increased brain expression in nest scouts, but was downregulated in food scouts; it also was downregulated in a previous study of scouts [15] and downregulated in active versus inactive foragers [22]. These results suggest differences in responsiveness to olfactory stimuli in the foraging and swarming contexts.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Perhaps differences in the expression of genes such as odour-binding protein 4 (obp4) reflect some of the differences in the sensory aspects of these two types of scouting. The gene obp4 showed increased brain expression in nest scouts, but was downregulated in food scouts; it also was downregulated in a previous study of scouts [15] and downregulated in active versus inactive foragers [22]. These results suggest differences in responsiveness to olfactory stimuli in the foraging and swarming contexts.…”
Section: Discussionmentioning
confidence: 59%
“…Three colonies were used to collect food scouts and recruits, and two colonies were used to collect nest scouts and recruits (one colony was used in both food and nest scouting experiments). All bees were foraging age, and collected only in the morning to eliminate possible age and circadian effects on brain gene expression, respectively [22,23].…”
Section: Materials and Methods (A) Beesmentioning
confidence: 99%
“…Such appointments form the essence of the honey bee time sense: foragers associate the presence of food with both location and time of day and then schedule anticipatory flights to the appropriate location and time on the following day (reviewed in Moore, 2001). Recently, such spatiotemporal memories have been shown to correspond with distinct neurogenomic signatures, as revealed by microarray analyses on time-trained foragers (Naeger et al, 2011). The results of the present study indicate that a forager's appointments do not have to occupy different time slots (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At the start of each replicate, the colony was moved into a large (20×6×3 m), outdoor, screened enclosure to control the time of food availability (Naeger et al, 2011). Every afternoon at 14:00-17:00 h CST a feeder containing 50% (w/v) sucrose solution was placed in the enclosure at the opposite end of the enclosure from the hive, coinciding with the time that mating flights begin for drones at this locality.…”
Section: Behavioral Manipulations and Bee Collectionsmentioning
confidence: 99%
“…As with drone mating flights, worker foraging flights also are under the control of an internal clock (Renner, 1957). Transcriptomic analyses revealed that different spatiotemporal foraging memories are associated with distinct patterns of brain gene expression, including genes that regulate circadian rhythms (Naeger et al, 2011). We used these two spatiotemporal flight behaviors in drone and worker honey bees to compare the patterns of gene expression in the brain associated with instinctive and learned behaviors.…”
Section: Introductionmentioning
confidence: 99%